The night ministry : facing the los of a founder - Cohn, Anne; Lo, Sara ([London] : SAGE, 2016)
Paul Hamann was senior vice president of The Night Ministry, a Chicago-based not-for-profit organization. In October 2003 he received a phone call from the wife of the Reverend Tom Behrens, the founding president and the public face of the organization. She told Hamann that Behrens had suffered a massive stroke and that doctors were unsure of his prognosis. Behrens had been walking the streets of run-down Chicago neighbourhoods since 1976, looking for people in despair, listening to their needs, and offering them a helping hand and a consoling presence. In the intervening 27 years, he had built The Night Ministry into a well-known organization that helped thousands of adults and youth every year. No succession plan, if one existed, had ever been conveyed to anyone at a senior level within the organisation. This case study discusses this topic.
Originally Published in: Donnelly, A. C., & Lo, S. (2012). The Night Ministry: Facing the Loss of a Founder. 5-112-004. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Night Ministry (Organization); Executive succession -- Case studies; Corporate governance -- Case studies; Nonprofit organizations -- Management -- Case studies